Defining sport : conceptions and borderlines - Klein, Shawn E., ....- (Maryland : Lexington Books, 2017)
Defining Sport: Conceptions and Borderlines is not about the variations of usage of the term “sport.” It is about the concept, the range of activities in the world that we unite into one idea—sport. It is through the project of defining sport that we can come to understand these activities better, how they are similar or different, and how they relate to other human endeavors. This definitional inquiry, and the deeper appreciation and apprehension of sport that follows, is the core of this volume. Part I examines several of the standard and influential approaches to defining sport. Part II uses these approaches to examine various challenging borderline cases. These chapters examine the interplay of the borderline cases with the definition and provide a more thorough and clearer understanding of both the definition and the given cases. This work is not meant to be the definitive or exhaustive account of sport. It is meant to inspire further thought and debate on just what sport is; how it relates to other activities and human endeavors; and what we can learn about ourselves through the study of sport. This book will be of interest to scholars in philosophy of sport, history, communications, sociology, psychology, sports management, cultural studies, and physical education.